Communicable Diseases Surveillance: CDI volume 29 issue 3 (2005) - No authors listed (Communicable Diseases Intelligence, 2005)
Communicable diseases surveillance outcomes from several reporting series as follows: Highlights for 2nd quarter, 2005 (gastrointestinal illnesses, quarantinable diseases, sexually transmissible infections, vaccine preventable diseases, other bacterial infections); National Notifiable Diseases Surveillance System tables, 1 April to 30 June 2005; Laboratory Serology and Virology Reporting Scheme tables, 1 April to 30 June 2005; Australian Sentinel Practice Research Network, reporting period 1 April to 30 June 2005 (cumulation of year to date); Australian childhood immunisation coverage, 1 January to 31 March 2005 cohort, assessed as at 30 June 2005; Gonococcal surveillance, reporting period 1 January to 31 March 2005; Meningococcal surveillance, reporting period 1 April to 30 June 2005; HIV and AIDS surveillance, reporting period 1 January to 31 March 2005, assessed as at 30 June 2005; National Enteric Pathogens Surveillance System, reporting period 1 April to 30 June 2005.